Visualization of the Goddess Hera Character as a Fantasy Dress with the Saviors Theme - Wahyuni, Siti; Puspitasari, Feny (Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, 2024)
Fantasy dress refers to clothing created through imagination or inspiration, often resembling original objects or ideas. These ideas typically stem from mythical figures such as the Goddess Hera, renowned in Greek mythology as the queen of the goddesses. Hera's regal character inspires fantasy dress designs, aligned with themes like